Jeneponto Smart Branding (JSB) Program Implementation in Jeneponto Regency, South Sulawesi Indonesia - Suci Megawati,; Mernawati,; Muhammad Farid Ma'ruf,; Trenda Aktiva Oktariyanda,; Deby Febriyan Oktariyanda,; Ahmad Nizar Hilmi, (Technium Social Sciences Journal, 2023)
This study aims to describe and analyze the implementation of JSB in Jeneponto Regency by exploring the context of the implementation of the JSB program. This study used descriptive qualitative method. Data collection techniques in research are observational interviews and FGDs. This study uses Qualitative Data Analysis. The results of the study show that the analysis of the implementation environment analysis is: a). The characteristics of the institution and regime in power, the Jeneponto District Head has an important role in the JSB program; b). The degree of change to be achieved is that the JSB program is long-term in nature and requires changes in people's behavior; c). Awareness and responsiveness, as a whole in the institution, organizational structure, committee or working group implementing the program; d). Local Wisdom, If the mindset changes and progresses to implementing JSB then it will become a support. The implementation model that has been implemented so far has not been optimal, so it is necessary to recommend a good program implementation model by optimizing the factors that influence the content of the policy and the Context of Implementation.